Does Technetium-99m Diethylenetriaminepentaacetate Clearance Predict the Clinical Course of Idiopathic Pulmonary Fibrosis? - Marco Mura; Gelorma Belmonte; Stefano Fanti; Angela Maria Pacilli; Luca Fasano; Maurizio Zompatori; Mario Schiavina; Mario Fabbri (Canadian Respiratory Journal)
Clearance of inhaled technetium-99m diethylenetriaminepentaacetate (99mTc-DTPA) is a potential indicator of disease activity and progression in idiopathic pulmonary fibrosis (IPF). The objective of the present study was to evaluate the prognostic value of 99mTc-DTPA scans in IPF. A total of 22 patients (18 males), aged 33 to 80 years with IPF were followed for six to 20 months (mean 13 months). At diagnosis, high resolution computed tomography (HRCT) scans showed a honeycomb pattern with bibasilar reticular opacities in all cases. At T0 (diagnosis) and T1 (follow-up), each patient had pulmonary function tests (forced vital capacity, diffusing capacity of the lung for carbon monoxide and partial arterial O2 pressure), extension of fibrosis evaluated by HRCT visual score and 99mTc-DTPA lung clearance. Results at T0 and T1 were compared, taking into account the whole population and patients with relatively fast and slow 99mTc-DTPA wash-out. 99mTc-DTPA clearance did not show any significant correlation with functional tests or HRCT score. These findings indicate that clearance of inhaled 99mTc-DTPA is not of value in following the progress of IPF.